2020
DOI: 10.1128/jvi.01901-19
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytomegalovirus Decreases Major Histocompatibility Complex Class II by Regulating Class II Transactivator Transcript Levels in a Myeloid Cell Line

Abstract: Human cytomegalovirus (HCMV) is a ubiquitous pathogen that encodes many proteins to modulate the host immune response. Extensive efforts have led to the elucidation of multiple strategies employed by HCMV to effectively block NK cell targeting of virus-infected cells and the major histocompatibility complex (MHC) class I-primed CD8+ T cell response. However, viral regulation of the MHC class II-mediated CD4+ T cell response is understudied in endogenous MHC class II-expressing cells, largely because the popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 71 publications
3
19
0
1
Order By: Relevance
“…Thus, we hypothesized that treatment of infected cells with GW4869 would also affect the spread of HCMV. We tested the effect of GW4869 at a low MOI using a recombinant TB40/E strain that encodes green fluorescent protein (GFP) adjacent to the viral immediate early protein 2 separated by the T2A peptide (36). During infection with this virus, GFP-positive cells can be used to monitor virus spread through the monolayer after addition of the EV inhibitor GW4869 or dimethyl sulfoxide (DMSO) vehicle control.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we hypothesized that treatment of infected cells with GW4869 would also affect the spread of HCMV. We tested the effect of GW4869 at a low MOI using a recombinant TB40/E strain that encodes green fluorescent protein (GFP) adjacent to the viral immediate early protein 2 separated by the T2A peptide (36). During infection with this virus, GFP-positive cells can be used to monitor virus spread through the monolayer after addition of the EV inhibitor GW4869 or dimethyl sulfoxide (DMSO) vehicle control.…”
Section: Resultsmentioning
confidence: 99%
“…Culture conditions were 37°C with 5% CO 2 . Wild-type TB40/E or the IE-2A-GFP derivative were used for all experiments (36). HCMV infections.…”
Section: Methodsmentioning
confidence: 99%
“…Further evidence in a transfected cell line model system showed that CMV downregulates MHC class II expression on the cell surface via regulation of CIITA and independently of known CMV Class II modulators US2 and US3 (Cebulla et al, 2002). Recently, it has also been shown in kasumi-3 cells, a myeloid lineage tumor cell line, that reduction in endogenous expression of MHC class II is as a result of decreased CIITA transcription (Sandhu and Buchkovich, 2020). UL23 binds to the Stat effector molecule N-myc, preventing proper activation and translocation of the Stat1 homodimers required for IFN-γ signaling (Feng et al, 2018), while UL31 preferentially binds the cytosolic DNA sensor cGAS in a manner that results in inhibition of interferon-associated gene transcription (Huang et al, 2018).…”
Section: Evasion Via Downregulation Of Class II Transcriptional Activmentioning
confidence: 99%
“…Inhibition of MHC-II expression by varicella-zoster has also been observed [ 90 , 91 ]. Repression of CIITA by human cytomegalovirus (HCMV) and Epstein–Barr virus has also been shown [ 92 , 93 , 94 , 95 ]. Interference with the IFNγ pathway has been observed in infections with influenza viruses [ 96 , 97 ].…”
Section: Ciita In Diseasementioning
confidence: 99%
“…This inhibition was also independent of previously known viral MHC-II repressor proteins that intervene in the IFNγ-induced expression, such as the tegument protein pp65, the viral IL-10 homolog, and two proteins coded from unique short (US) regions, US2 and US3, failed to downregulate MHC-II expression. Single gene knock-out studies failed to find a responsible gene in the US region, thus suggesting that the cause may be a complex interaction of several proteins in this region or that the responsible factor is coded elsewhere [ 95 ].…”
Section: Ciita In Diseasementioning
confidence: 99%